The subversion of toll-like receptor signaling by bacterial and viral proteases during the development of infectious diseases. (December 2022) - Ciaston, Izabela; Dobosz, Ewelina; Potempa, Jan; Koziel, Joanna
Abstract: Toll-like receptors (TLRs) are pattern recognition receptors (PRRs) that respond to pathogen-associated molecular patterns (PAMPs). The recognition of specific microbial ligands by TLRs triggers an innate immune response and also promotes adaptive immunity, which is necessary for the efficient elimination of invading pathogens. Successful pathogens have therefore evolved strategies to subvert and/or manipulate TLR signaling. Both the impairment and uncontrolled activation of TLR signaling can harm the host, causing tissue destruction and allowing pathogens to proliferate, thus favoring disease progression. In this context, microbial proteases are key virulence factors that modify components of the TLR signaling pathway. In this review, we discuss the role of bacterial and viral proteases in the manipulation of TLR signaling, highlighting the importance of these enzymes during the development of infectious diseases.